2018
DOI: 10.1038/s41390-018-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

The premature infant gut microbiome during the first 6 weeks of life differs based on gestational maturity at birth

Abstract: BackgroundThe impact of degree of prematurity at birth on premature infant gut microbiota has not been extensively studied in comparison to term infants in large cohorts.MethodsTo determine the effect of gestational age at birth and postnatal exposures on gut bacterial colonization in infants, we analyzed 65 stool samples from 17 premature infants in the neonatal intensive care unit, as well as 13 samples from 13 mostly moderate-to-late premature infants and 189 samples from 176 term infants in the New Hampshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
125
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 31 publications
15
125
1
2
Order By: Relevance
“…Furthermore, a more recent study of preterm infant gut microbiome supported the previously mentioned studies that only GA at birth but not antibiotic exposure in the first few days of life nor mode of delivery significantly impact the bacterial alpha-diversity among preterm infants (Chernikova et al, 2018). This study demonstrated that vaginal delivery was associated with greater Bacteroides abundance agreeing with most of the studies in term infants, but had no significant effects in preterm infants on bacterial abundance of Streptococcus, Bacteroides, and Lactobacillus (Chernikova et al, 2018). It is worth emphasizing the low enrollment number of spontaneous vaginal delivery of preterm term infants in these studies; thus, emerging studies with more patients might yield more precise insight into the impact of delivery mode on preterm infant microbiota.…”
Section: Factors Influencing the Assemblysupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, a more recent study of preterm infant gut microbiome supported the previously mentioned studies that only GA at birth but not antibiotic exposure in the first few days of life nor mode of delivery significantly impact the bacterial alpha-diversity among preterm infants (Chernikova et al, 2018). This study demonstrated that vaginal delivery was associated with greater Bacteroides abundance agreeing with most of the studies in term infants, but had no significant effects in preterm infants on bacterial abundance of Streptococcus, Bacteroides, and Lactobacillus (Chernikova et al, 2018). It is worth emphasizing the low enrollment number of spontaneous vaginal delivery of preterm term infants in these studies; thus, emerging studies with more patients might yield more precise insight into the impact of delivery mode on preterm infant microbiota.…”
Section: Factors Influencing the Assemblysupporting
confidence: 69%
“…For preterm infants, several studies have reported that the mode of delivery does not influence the bacteria diversity difference between preterm and term infants (Dahl et al, ; Hill et al, ). Furthermore, a more recent study of preterm infant gut microbiome supported the previously mentioned studies that only GA at birth but not antibiotic exposure in the first few days of life nor mode of delivery significantly impact the bacterial alpha‐diversity among preterm infants (Chernikova et al, ). This study demonstrated that vaginal delivery was associated with greater Bacteroides abundance agreeing with most of the studies in term infants, but had no significant effects in preterm infants on bacterial abundance of Streptococcus , Bacteroides , and Lactobacillus (Chernikova et al, ).…”
Section: Factors Affecting the Assembly Of Neonatal Gut Microbiotasupporting
confidence: 54%
“…A recent study, utilizing 16S rRNA gene sequencing, revealed that bacterial alpha diversity varies based on the infants' gestational age, with more premature infants having less diverse microbiomes. This study also showed that infants born at a later gestational age had greater abundance of Bifidobacterium and Streptococcus 10 . However, there were no analyses of differences in metabolic potential of microorganisms colonizing infants of different gestational age, due to the low resolution of the 16S method.…”
Section: Introductionsupporting
confidence: 64%
“…In a Northern American study that included fecal samples obtained from 30 premature and 176 term infants at 6 weeks of age 65 reduced alpha diversity was found in preterm vs term infants even after adjusting for exposures. 65 In addition, in preterm vs term infants a reduced abundance of Bacteroides (7% vs 19), Bifidobacterium (3% vs 15%), and Streptococcus (2% vs 9%) 65 was observed. Interestingly prematurity is reported to be a risk factor for ERA (OR 1.9, 95% CI:…”
Section: Other Environmental Factors Affecting Microbiota Colonizationmentioning
confidence: 96%